Awareness, risk for cervical cancer and readiness for Papanicolaou (Pap) testing among female housekeeping staff in a tertiary care hospital Karnataka-A quantitative approach - Sushma Belinda Rodrigues; Melita Sheilini; Raghavendra Nayak (Elsevier, 2024)
Problem considered: Cervical cancer is the second most prevalent cancer in India and the fourth most common cancer globally. The lack of awareness surrounding cervical cancer creates challenges in achieving early detection and timely screening. The study aimed to assess the awareness about cervical cancer, to identify the risk for cervical cancer, and to assess the readiness for Pap testing. Methods: A descriptive survey design was adopted among female housekeeping staff in a tertiary care hospital in Udupi district, Karnataka. A total of 340 female housekeeping staff were selected based on the purposive sampling technique. Data was collected using structured questionnaires developed by the researcher that were self-administered to the participants and analysis was done using both descriptive and inferential statistics. Results: Out of 340, the majority 210(61.8%) had poor awareness on cervical cancer and 310(91.2%) were ready for Pap test. The top five self-reported risk factors among the participants were: partners not using condoms during sexual intercourse 326(95.9%), partners not circumcised 325(95.6%), given birth 312(91.2%), had not undergone regular Pap test for screening cervical cancer 291(85.6%), and being sexually active 137(40.3%). There was a significant association between awareness and variables like attainment of menopause (χ2 = 8.28, p = 0.016), and heard about cervical cancer (χ2 = 21.8, p=<0.001). Conclusion: The study findings highlight the importance of an awareness program on cervical cancer since most of the participants had high readiness for pap tests regardless of poor awareness. Hence the participants were motivated to undergo screening tests through the awareness program conducted in small groups.